2011
DOI: 10.1038/nature10108
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis for fluorination and trifluoromethylation

Abstract: Preface Recent advances in catalysis have made the incorporation of fluorine into complex organic molecules easier than ever before, but selective, general, and practical fluorination reactions remain sought after. Fluorination of molecules often imparts desirable properties such as metabolic and thermal stability, and fluorinated molecules are therefore frequently used as pharmaceuticals or materials. Even with the latest advances in chemistry, carbon–fluorine bond formation in complex molecules is still a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
635
0
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,975 publications
(651 citation statements)
references
References 103 publications
1
635
0
15
Order By: Relevance
“…and found that the corresponding L 1 -X coupling products were obtained quantitatively ( [37][38][39] . DFT calculations show that the reductive elimination of L 5 -Ag(III) is strongly exergonic (DG ¼ À 25.8 kcal Á mol À 1 ) and has a very low barrier (DG a ¼ 8.6 kcal Á mol À 1 ; for computed reaction profile see Supplementary Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms5373mentioning
confidence: 99%
“…and found that the corresponding L 1 -X coupling products were obtained quantitatively ( [37][38][39] . DFT calculations show that the reductive elimination of L 5 -Ag(III) is strongly exergonic (DG ¼ À 25.8 kcal Á mol À 1 ) and has a very low barrier (DG a ¼ 8.6 kcal Á mol À 1 ; for computed reaction profile see Supplementary Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms5373mentioning
confidence: 99%
“…Trifluoromethylated arenes are important motifs in many pharmaceuticals, agrochemicals and organic materials due to the strong electron-withdrawing nature and the large hydrophobic domain of a CF 3 -group [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…O rganic compounds containing trifluoromethyl (CF 3 ) group(s) are versatile components of drugs, agrochemicals and organic materials. The CF 3 group is highly electron withdrawing, and its introduction can remarkably improve molecular properties, such as lipophilicity, metabolic stability and bioavailability 1 .…”
mentioning
confidence: 99%
“…The CF 3 group is highly electron withdrawing, and its introduction can remarkably improve molecular properties, such as lipophilicity, metabolic stability and bioavailability 1 . Therefore, the development of an efficient trifluoromethylation process is currently a main topic in organic synthesis [2][3][4][5][6][7][8][9] . Most current processes for accessing CF 3 containing molecules are performed by carboxy or trichloromethyl group substitution using hazardous fluorinating reagents under harsh reaction conditions 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation